Electric Multiple Unit of Skoda 16Ev Series (Current Problems in Rail Vehicles, 2021)
The contribution deals with the description of the electric unit type 16Ev from the production of ŠKODA TRANSPORTATION a.s. / ŠKODA VAGONKA a.s. The electric multiple unit will be put into operation on wide gauge lines in Latvia. The train will be operated by the Latvian Railways (Pasažieru vilciens).
Keywords: electric multiple unit; EMU; Škoda 16Ev; Latvian railways (PV)